Microbiology of infective endocarditis in Hong Kong from 2000 to 2019: a 20-year analysis. (14th October 2021) - Li, H L; Tse, Y K; Yu, S Y; Wu, M Z; Ren, Q W; Tse, H F; Yiu, K H
Abstract: Background: Infective endocarditis (IE) is associated with high mortality and complex microbiological profile. The antibiotic prophylaxis guidelines underwent a major revision in 2009 to reduce unnecessary antibiotic exposure. Substantial geographic variations in microbiological profiles exist, of which the understanding in an Asian population is lacking. Purpose: We aim to describe the trends in the microbiology of IE in Hong Kong in the past 2 decades. Methods: All patients aged 20 or above diagnosed with incident IE with blood culture results from 2000–2019 were included from a well-validated territory-wide database in Hong Kong, and were classified as 7 groups of causative organisms as shown in Figure 1. To evaluate the association between microbiology and 1-year all-cause death, a multivariable Cox proportional-hazards model was used, adjusted with demographics and comorbidities. Temporal trends in the proportion of each organism were characterised using Poisson regression. Interrupted time series analysis was used to evaluate the change in the organism-specific incidence after the revision of guidelines. Results: In a total of 5, 657 patients (age 59.9±18.3 years, 37.2% females), there were 2, 185 (38.6%) patients with culture-negative endocarditis. Staphylococcus aureus (22.4%) and Streptococci (20.5%) were the most common organisms identified. Over time, there was a significant reduction in the proportion of culture-negative endocarditis (annual percentage change [APC] −2.3% [−2.8 to −1.7], P<0.001), and a significant increase in the proportion of endocarditis due to Staphylococcus aureus (APC 1.6% [0.7 to 2.4], P<0.001) and Streptococci (APC 2.3% [1.4 to 3.3], P<0.001) (Figure 1). After guidelines revision in 2009, there was no significant change in organism-specific incidence (all P-values for relative change>0.05). Compared to patients with culture-negative endocarditis, those infected with Staphylococcus aureus (hazard ratio [HR] 2.19 [1.94–2.47], P<0.001), other Staphylococci (HR 1.56 [1.20–2.01], P<0.001), Enterococci (HR 1.60 [1.25–2.05], P<0.001), other microorganisms (HR 1.30 [1.05–1.60], P=0.015), and mixed microorganisms (HR 2.40 [2.02–2.84], P<0.001) had a higher risk of 1-year all-cause death (Figure 2). There was a significant increase in the proportion of methicillin-resistant Staphylococcus aureus (MRSA) endocarditis (APC 4.1% [1.9 to 6.3], P<0.001), with no significant interval change after 2009. Patients infected with MRSA had a higher all-cause death (HR 2.00 [1.70–2.36], P<0.001). Conclusions: Different causative organisms carry variable mortality signals in infective endocarditis. Over time, there were fewer cases of culture-negative endocarditis, and the revision of antibiotic prophylaxis guidelines did not result in a significant change in the microbiological profile. There was an increasing trend for MRSA endocarditis, which was associated with a higher risk of death. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The Shenzhen Key Medical DisciplineThe Sanming Project of HKU-SZH Cardiology